La crisis del indigenismo clásico y el surgimiento de un nuevo paradigma sobre la población indígena de México - Sanz Jara, Eva (Revista Complutense de Historia de América, 2010)
The Mexican Revolution resulted in the implementation of the ideology of crossbreeding and integrationist indigenism, which defended the convenience of integration of indigenous people into the national society. But in the late 60s, in the context of widespread international protests, widespread criticism of government policies began in all fields, where disagreements regarding classical indigenism and integration were of special significance. The Tlatelolco massacre of 1968 was to be a turning point in the atmosphere of revolt against the established power. Shortly thereafter, stronger criticism helped to generate an alternative with respect to the treatment to the Indians, leading to a new paradigm that might be called pluralist or multicultural. This paper will describe the successive paradigms that have taken place since the Mexican Revolution with respect to indigenous people, with the aim of drawing some conclusions from the observed changes. The paper will also try to espouse some explanations about the observed change of ideology, in order to establish a comparison between this and the previous one, as well as assessing the extent of that change.
Keywords: Anthropology; Indigenous; Discourse; Classical Indigenism; Integrationism; Pluralism; Multiculturalism; Identity Policies; Zapatismo; Mexico; 20th Century